Characterisation of resonant structure of relativistic magnetron - Maurya S.; Singh V.V.P.; Jain P.K. (My University, 2025)
The authors describe a systematic analysis of relativistic magnetron interaction structure and operating characteristics. The authors have plotted the admittance curves for resonator and interaction space to predict the possible resonant frequency of a relativistic magnetron for the π-mode. Hull cut-off Parabola and Buneman-Hartree resonance curves have also been plotted for the resonant structure of a relativistic magnetron using MATLAB. A three-dimensional particle-in-cell (PIC) code, MAGIC3D, is used to simulate the oscillation spectrum, dispersion diagram and the resonant frequency of the resonant structure. A comparative study of simulated eigenmode frequency and calculated from admittance matching criteria has also been performed. © 2012 The Institution of Engineering and Technology.